Determinants of the early initiation of breastfeeding in the Kingdom of Saudi Arabia - Adam E. Ahmed; Osama A. Salih (BMC, 2019)
Abstract Background National surveys in the Kingdom of Saudi Arabia continue to show rates of breastfeeding below global recommendations. Delay of timely or early initiation of breastfeeding is common in the community. Current approaches are not addressing the major constraints. Objectives of this study were to study the pattern and determinants associated with the early and delayed initiation of breastfeeding practices among infants aged less than 24 months. Also to assess regional differences to facilitate targeted actions. Methods This cross-sectional study was conducted from May to August 2016, based on a sample of 1700 mothers of children aged less than 24 months. The sample was randomly selected from over 165 health centers distributed across the country, at least 33 centers in each of the five geographical regions. World Health Organization standardized questionnaire for infant and young child feeding indicators was used to prepare structured questionnaire (in English translated later to Arabic) to collect the information on breastfeeding along with general sociodemographic data. Results The breastfeeding initiation rate was 97.3% (1559/1700 mothers). Only 8.3% (141) of mothers never breastfeed their children. Early initiation of breastfeeding within 1 h of birth was 43.6% (742) among all mothers surveyed while, breastfeeding initiation rates for 1-24 h and that for more than 24 h were 27 and 21% respectively. The overall prevalence of early initiation of breastfeeding (43.6%) is considered 'fair'. Regional variation showed poor prevalence 26% (79/300 mothers) in Northern region; fair 38.4% (192/500 mothers), 45% (135/300 mothers), 49% (148/300 mothers) in the Central, Western and Eastern regions respectively; and good 63% (188/300 mothers) in the Southern region. Significant associations were indicated between early initiation of breastfeeding and mode of delivery, knowledge of the mother about the right time for early initiation, receipt of breastfeeding information, the region of residence, and educational level of the mother. Conclusion Whilst some barriers to breastfeeding initiation manifest similarity across the regions some factors were context-specific thus, tailored interventions are imperative. Appropriate behavior change interventions, are needed attain optimal breastfeeding practices.